The sword of Medina : a novel - Jones, Sherry, 1961- (Beaufort Books, 2009)
Before dying, Muhammad left his jeweled sword, al-Ma'thur, to A'isha, telling her to use it in the jihad to come. But what if the jihad is against her own people? After 20 years of distrust and anger, can A'isha and Ali come together to preserve the future of their people and their faith--or will their hatred of each other destroy everything Muhammad worked to build? This climactic sequel to the controversial [i]The Jewel of Medina[/i] returns to 7th century Arabia to discover whether, after fighting a civil war, a people can ever truly heal.